Utility of Sleep Questionnaires for Detecting Sleep Apnea in Ischemic Stroke Patients - S Mythirayee; Dipti Baskar; G Seethalakshmi; Ravi Yadav; Nitish L Kamble; Girish Baburao Kulkarni; Sanjib Sinha; Pooja Mailankody; PR Srijithesh (Annals of Indian Academy of Neurology)
Background and Objectives: Sleep-disordered breathing is highly prevalent in stroke patients. It is associated with recurrence of stroke and poor neurologic outcomes. Polysomnography (PSG), the gold standard for diagnosing sleep apnea, may not be feasible for routine evaluation in stroke patients. There is a need for reliable screening tools to assess the likelihood of sleep apnea in these patients. This study evaluated the efficacy of sleep questionnaires to predict the likelihood of sleep apnea against PSG-determined sleep apnea. Methods: A hospital-based study on ischemic stroke patients used the content-validated Kannada version of Berlin Questionnaire, STOP-BANG questionnaire, and Epworth Sleepiness Scale (ESS). All patients underwent overnight PSG, scored by blinded investigators, to assess the diagnostic properties of the questionnaires for various apnea–hypopnea index cutoffs. Results: The study included 70 Kannada-speaking patients with a mean age of 50.9 years. The study revealed a high prevalence of sleep apnea (80%), with obstructive sleep apnea being the most common type (77.5%). The Berlin Questionnaire showed modest sensitivity (0.51) and specificity (0.60), while the STOP-BANG questionnaire demonstrated moderate sensitivity (0.64) and specificity (0.70). The mean ESS scores were 6.6 (standard deviation [SD] 5.9) for patients with sleep apnea and 4.3 (SD 3.1) for those without sleep apnea. Conclusion: Sleep questionnaires lacked the necessary diagnostic properties to serve as standalone screening tools for sleep apnea in ischemic stroke patients. Future research should aim to develop or improve screening instruments specifically designed for stroke patients.